Wellbeing Alternative Policy Perspectives - Besley, Timothy; BUCELLI, IRENE (LSE Press, 2022)
Governments in liberal democracies pursue social welfare, but in many different ways. The wellbeing approach instead asks: Why not focus directly on increasing measured human happiness? Why not try to improve people's overall quality of life, as it is subjectively seen by citizens themselves? The radical implications of this stance include shifting attention to previously neglected areas (such as mental health and 'social infrastructure' services) and developing defensible measures of overall wellbeing or quality of life indicators. Can one 'master' concept of wellbeing work to create more holism in policy-making? Or should we stick with multiple metrics? These debates have been live in relation to an alternative 'capacities' approaches, and they are well-developed in health policymaking. Most recently, the connections between wellbeing and political participation have come into sharper focus. Wellbeing remains a contested concept, one that can be interpreted and used differently, with consequences for how it is incorporated into policy decisions. By bringing together scholars from economics, psychology and behavioural science, philosophy and political science, the authors explore how different disciplinary approaches can contribute to the study of wellbeing and how this can shape policy priorities.